Effectiveness of Triamcinolone Injections in Preventing Scar Deformity following Endoscopic Submucosal Dissection for Pharyngeal Cancer - Yugo Suzuki; Shinji Ito; Tsuyoshi Ishii; Minoru Oda; Shu Hoteya (Case Reports in Gastroenterology)
Introduction: Endoscopic submucosal dissection (ESD) is an effective treatment for superficial pharyngeal cancer. However, pharyngeal deformity caused by postoperative ulcer contraction is a major concern and can result in a poor quality of life. While local steroid injections have been shown to prevent strictures after ESD for esophageal cancer, their effectiveness in preventing deformities following ESD for pharyngeal cancer remains unclear. Case Presentation: A 60-year-old woman with superficial pharyngeal cancer in the left pyriform sinus underwent ESD. After ESD, 80 mg of triamcinolone acetonide was injected into the ulcer bed to prevent scar contracture. The patient experienced mild pharyngeal pain, which resolved within a few days. Histopathological examination confirmed the lesion was well-differentiated SCC, with negative resection margins and no lymphovascular invasion. Follow-up endoscopy at 6 weeks showed granulation tissue in the surgical wound, which completely healed without pharyngeal deformity by 14 weeks post-ESD. Conclusion: This case demonstrated that the injection of triamcinolone in an ulcer that developed after ESD may be an effective method of preventing pharyngeal deformity caused by scar contracture.